97 Medical grand rounds – assessing the impact and improving attendance. (12th November 2018) - Edwards, Helena; Laird, Amanda; Burton, Zoe; Hobson, Alex
Abstract : Introduction: Medical grand rounds are a well-established form of postgraduate medical education and are still a component of most UK hospital teaching programmes. Our large acute district general hospital runs a weekly grand round, which is open to all clinicians. Aims: Attendance at grand round has gradually reduced over the preceding years in our hospital, which is also reflected nationally. The aim of this project was to assess the reasons for the decline in attendance and then implement changes that led to a sustained improvement. Methods: A 10-item questionnaire was developed to assess whether grand round still provided an effective learning opportunity and to identify factors affecting attendance. There were 98 respondents from a variety of medical grades. The majority of respondents did not attend grand round on a regular basis, however there was enthusiasm for grand round with 68% of respondents saying that it provided an effective learning environment. A number of factors affecting attendance were identified including workload and clinical commitments, logistical issues such as inconsistent venue and lack of refreshments, and culture. These were addressed with a number of interventions such as posters for advertising, drug rep sponsorship, the use of high profile speakers and attempts to improve the culture. Results: The improvement strategy has been a continuous project over the last year from September 2017. Attendance of grand round has been monitored using a sign-in register for each session. Written feedback was also collected from each session to allow us to develop future programmes. The results have shown a gradual, but consistent increase in attendance at grand round from an average of 16 attendees to 36.